Kar Kar and migration in Mali - (:unkn) unknown (My University, 2013)
Panel Words, arts and migration in Africa: narrative, mod. Marina Lafay et Carola Mick http://www.nomadit.co.uk/ecas/ecas2013/panels.php5?PanelID=1875
Keywords: African Research